Transformation of Multiple Representations in Understanding Real-World Physics Problems - Murshed, Mazlena; Aliah Phang, Fatin; Abd Hadi Bunyamin, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to investigate the transformation of multiple representations (MRs) in explaining the physics related to real-world situations, for example, when a ball is thrown vertically upwards. The transformation of MR is investigated using one-to-one thinking-aloud problem-solving among five Form Four students from a few secondary schools in Johor, Malaysia. Later, a retrospective interview was carried out to understand the function and the meaning given by students towards the representation they made. Analyses of the students’ solutions reveal how MRs are utilized to explain the characteristics of the situation given. The studies revealed that the majority of students employed texts, sketches, and symbols to illustrate the ideas of the motion of the ball, the energy contained, and the force in action. Backed by the results, it was suggested to use the transformation of multiple representations to improve students’ understanding of the problem related to real-world situations.